2021
DOI: 10.3389/fimmu.2021.654623
|View full text |Cite
|
Sign up to set email alerts
|

Human PD-1hiCD8+ T Cells Are a Cellular Source of IL-21 in Rheumatoid Arthritis

Abstract: BackgroundRheumatoid arthritis (RA) is a prototypical autoantibody-driven autoimmune disease in which T-B interactions play a critical role. Recent comprehensive analysis suggests that PD-1+CD8+ T cells as well as two distinct IL-21-producing PD-1+CD4+ T cell subsets, follicular helper T (Tfh) and peripheral helper T (Tph) cells, are involved in the pathogenesis of RA. Herein, we aimed to clarify a generation mechanism of IL-21-producing CD8+ T cells in humans, and to characterize this novel subset in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…We have shown that the CD4 + CD20 + T cell population is enriched with TFH and TPH; CD8 + CD20 + T cells also harbor subsets with similar features to TFH and TPH. In agreement with suggestions in RA (66), our data suggest that CXCR5 + PD-1 + CD8 + T cells CXCR5 -PD-1 + CD8 + T cells in concert with TFH and TPH play an essential role in augmenting pathology in CIA. The capacity of CD4 + CD20 + T cells to induce the expansion of cognate B cells and the production of class-switched antibodies warrants investigation.…”
Section: Tph Cells Have Been Implicated In Interactions Between T-b Cell Collaboration Located Adjacentsupporting
confidence: 92%
See 1 more Smart Citation
“…We have shown that the CD4 + CD20 + T cell population is enriched with TFH and TPH; CD8 + CD20 + T cells also harbor subsets with similar features to TFH and TPH. In agreement with suggestions in RA (66), our data suggest that CXCR5 + PD-1 + CD8 + T cells CXCR5 -PD-1 + CD8 + T cells in concert with TFH and TPH play an essential role in augmenting pathology in CIA. The capacity of CD4 + CD20 + T cells to induce the expansion of cognate B cells and the production of class-switched antibodies warrants investigation.…”
Section: Tph Cells Have Been Implicated In Interactions Between T-b Cell Collaboration Located Adjacentsupporting
confidence: 92%
“…A recent report showed that PD-1 + CD8 + T cells also produce increased amounts of IL-21 that allow B cell differentiation; these cells were abundant in RA patients' peripheral blood and synovial fluid. Of note, the PD-1 + CD8 + T cell subset expressed CCR2 but not CXCR5 (66).…”
Section: Tph Cells Have Been Implicated In Interactions Between T-b Cell Collaboration Located Adjacentmentioning
confidence: 93%
“…The degree of macrophage infiltration in joint tissues and the level of monocytederived cytokines in serum show positive correlations to disease severity (7). CD8+ T cell exhibits anti-inflammation characteristic and is likely to contribute to the reduction of persistent autoimmune responses in rheumatoid joints (8,9). B cells impact bone remodeling in RA (10).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CD8 T cells of any subsets express higher levels of IFN-c than any CD4 T cells in RA joint. Regarding PD-1þ CD8 T cells in RA joint, we recently found them producing IL-21 and not expressing CXCR5, similar to Tph cells [90]. An association between ELN formation in the synovium and the presence of CD8 T cells expressing CD40L was also shown [91].…”
Section: Functions Of Cd8 T Cells In Ra Jointmentioning
confidence: 70%